Analysis of E-Wom Effectiveness in Celebrity Cancel Culture Action on Sosial Media X - Luthfiyah, Finna Nazmi (Jogjakarta Communication Conference (JCC), 2024)
This research examines the effectiveness of Electronic Word of Mouth (E-WOM) in the cancel culture phenomenon against celebrities on social media X, focusing on controversial cases involving Kpop idols and the cancel culture movement related to the